Evaluating the Readability of Veterinary Client Handouts from Vetlexicon, Veterinary Partner, and ClientEd - Isabella Baxter; Ann Viera (Issues in Science and Technology Librarianship)
Ready-to-use animal health information handouts are a valuable service that have the potential to enhance veterinarian-client relationships and animal healthcare. Evaluating the readability of handouts is integral to ensure the information needs of veterinary clients are met. In this study, we describe the significance of client handout readability and review readability studies in veterinary medicine. We then present our analysis of the readability of 150 client handouts from three services: Vetlexicon from Vetstream, Veterinary Partner from VIN, and ClientEd from Lifelearn. With a few exceptions, the handouts scored were found to be written at a 9th through 11th grade reading level, above the recommended 6th grade reading level for human medical handouts, limiting the value and potential for enhancing communication about pet health and supporting the veterinarian-client bond.